Sensitization of Candida albicans biofilms to various antifungal drugs by cyclosporine A - Shinde Ravikumar B; Chauhan Nitin M; Raut Jayant S; Karuppayil Sankunny M (BMC, 2012)
Abstract Background Biofilms formed by Candida albicans are resistant towards most of the available antifungal drugs. Therefore, infections associated with Candida biofilms are considered as a threat to immunocompromised patients. Combinatorial drug therapy may be a good strategy to combat C. albicans biofilms. Methods Combinations of five antifungal drugs- fluconazole (FLC), voriconazole (VOR), caspofungin (CSP), amphotericin B (AmB) and nystatin (NYT) with cyclosporine A (CSA) were tested in vitro against planktonic and biofilm growth of C. albicans. Standard broth micro dilution method was used to study planktonic growth, while biofilms were studied in an in vitro biofilm model. A chequerboard format was used to determine fractional inhibitory concentration indices (FICI) of combination effects. Biofilm growth was analyzed using XTT-metabolic assay. Results MICs of various antifungal drugs for planktonic growth of C. albicans were lowered in combination with CSA by 2 to 16 fold. Activity against biofilm development with FIC indices of 0.26, 0.28, 0.31 and 0.25 indicated synergistic interactions between FLC-CSA, VOR-CSA, CSP-CSA and AmB-CSA, respectively. Increase in efficacy of the drugs FLC, VOR and CSP against mature biofilms after addition of 62.5 μg/ml of CSA was evident with FIC indices 0.06, 0.14 and 0.37, respectively. Conclusions The combinations with CSA resulted in increased susceptibility of biofilms to antifungal drugs. Combination of antifungal drugs with CSA would be an effective prophylactic and therapeutic strategy against biofilm associated C. albicans infections.